2018
DOI: 10.1111/ijfs.13966
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis of anti‐hyperglycaemic effects of Pu‐erh tea

Abstract: Summary Pu‐erh tea was presumed to have anti‐hyperglycaemic effects with limited evidence. This study uses meta‐analysis to investigate anti‐hyperglycaemic effect of Pu‐erh tea. Five English databases and three Chinese ones were systematically searched up to July 31, 2018. Those databases were searched to identify studies containing keywords of ‘Pu‐erh’, ‘Pu'er’, ‘blood sugar’, ‘blood glucose’ and ‘hyperglycaemia’. RevMan 5 and Stata were then utilized to conduct meta‐analysis. Systematic reviews collected two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The chemical constituents of tea include polyphenols, polysaccharides, amino acids, alkaloids, volatile oils, vitamins, and so on (Pastoriza et al., 2017). Tea polysaccharide (TPS), as one of the main components of tea extract, has many beneficial biological activities, including antioxidation (Karadag et al., 2019), antidiabetic (Lin et al., 2019), anticancer (Nie, Xie, Zhou, & Cao, 2007), antiatherogenic effects (Zhou et al., 2007), and immunomodulatory activity (Monobe, Ema, Kato, & Maeda‐Yamamoto, 2008; Scoparo et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The chemical constituents of tea include polyphenols, polysaccharides, amino acids, alkaloids, volatile oils, vitamins, and so on (Pastoriza et al., 2017). Tea polysaccharide (TPS), as one of the main components of tea extract, has many beneficial biological activities, including antioxidation (Karadag et al., 2019), antidiabetic (Lin et al., 2019), anticancer (Nie, Xie, Zhou, & Cao, 2007), antiatherogenic effects (Zhou et al., 2007), and immunomodulatory activity (Monobe, Ema, Kato, & Maeda‐Yamamoto, 2008; Scoparo et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Pu-erh tea’s distinctive effects could potentially be attributed to a series of complex changes in chemicals during post-fermentation stage. These complex chemical changes in turn were found to lead to pu-erh’s great health benefits, such as lower atherosclerotic risk 5 , weight reduction 6 , and anti-hyperglycaemic effect, especially 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was found that ripened pu-erh tea had a better effect than raw pu-erh tea on the control of postprandial blood glucose in T2DM mice [67]. Additionally, pu-erh tea polysaccharides promoted adipocyte differentiation and glucose uptake by mimicking the properties of PPARγ and glucose transporter type 4 (GLUT4), ameliorating insulin resistance and lowering blood sugar [68]. Furthermore, Fu brick tea attenuated insulin resistance by down-regulating signal regulatory protein-α (SIRP-α) expression and activating insulin signaling in a Akt/GLUT4/FoxO1 and the target of rapamycin (mTOR)/S6K1 pathways in the skeletal muscle of male Sprague−Dawley rats [69].…”
Section: Experimental Studiesmentioning
confidence: 99%